Ummi method in Al-Qur'an learning management for strengthening students' religious character - Vidiana, Vina; Janah, Nasitotul (UIN Salatiga, 2025)
This study aims to determine the implementation, quality management, supporting and inhibiting factors, and the implications of the Ummi method of Al-Qur'an learning management in strengthening the religious character of students in leading public and private junior high schools in Magelang City. This study uses a qualitative method with multiple case study. Data collection techniques use interviews, observations and documentation studies. The results show; first, the implementation of this program in SMP Negeri 2 Magelang and SMP IT Ihsanul Fikri has gone through good stages, namely; planning, organizing, actuating, and controlling. Second, the quality management of both schools is categorized as good and fulfilled the requirements of 10 pillars Ummi quality system. It is relevant to Total Quality Management which focuses on customers and continuous improvement. Third, the supporting factor in SMP N 2 Magelang is the full support from management to maintain quality as religious school and the inhibiting factor is the lack of time allocation. Meanwhile, at SMP IT Ihsanul Fikri in Magelang City, the supporting factor is an integrated curriculum with the Quran and character development, which maximizes time allocation. Meanwhile, the inhibiting factor is the slow learner students. Fourth, the implications of this program at both schools are very positive in strengthening the students' religious character. It is an important foundation for preventing some problems faced by teenagers today.